The Analysis of Relationship Between Work Life Quality and Work Motivation of Non-Medical Employees in Regional General Hospital - Fatkhuri Fatkhuri; Qurnia Fitriyatinur; Asep Suherman; Hartanto; Roy Setiawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to identify the aspects of non-medical workers' work motivation that are related to their quality of work life. This study is quantitative and cross-sectional in nature. 74 non-medical staff made up the study's sample. Random proportional sampling was used for sampling. According to the findings of the research, there are 20 non-medical employees with low work motivation (27.0%), and there are 54 employees with high work motivation (73.0%). The availability of facilities, communication, career advancement, problem-solving skills, a sense of job stability, pride in one's workplace, job restructuring, and the environment all contribute to one's ability to stay motivated at work.